Quality assessment of selected herbal bath herbs based on drying methods and storage duration - Md Zuki, Rose Fazila (2021)
Herbal cultivation in Malaysian has been practiced for multiple ways of use. The issue in the herbal industry mainly is inadequacy of raw materials due to the lack of herb cultivation areas, though small to medium scale herbs farm existed, the supply of herbs still insufficient. Besides that, most of herbal products on the market are also not scientific research based, thus the use of them does not safety guaranteed. Therefore, to face this issue, herbal cultivation, also research and development of herbs needs to be enhanced, in order to produce optimum local herbal raw material and to ensure the quality for local herbal production. There were seven selected herbs for this study, namely Etlingera elatior (Torch ginger), Alpinia galanga (Greater galangal), Pandanus amaryllifolius (Pandan), Cymbopogon nardus (Citronella grass), Lawsonia inermis (Henna), Citrus hystrix (Kaffir Lime) and Piper betle (Betel leaves). The evaluation of herbs growth made based on cultivation in the herbal garden concept at different locations, also its quality assessment as herbal bath. The herbal garden concept was replicate at three different areas; Institute of Bio-Science, UPM, Kg. Sg. Serdang, Klang and Kg. Ulu Chuchoh, Sepang in Selangor. After all herbs reached maturity stage, found that citronella grass, pandan, henna, betel and kaffir lime had no significant difference in growth performance but torch ginger had significant difference in plant height, leaves size and fresh weight planted in herbal garden concept at these three areas. Herbal bath produced by combination of these herbs. The assessment of herbal bath quality based on the effect of drying, storing and period of storage, towards their production of essential oil. The herbs were dried under sun and in an oven (50oC), then stored in air-conditioner (AC) room, chiller and freezer for 360 days. As a result, the oven dried herbs had bright, attractive colour and possessed mild aromatic fragrant compared to sun dried herbs, besides took longer time (day) to dry, it also had dull, pale colour and possessed slightly smoke leaves scent. Next, quality of oven dried herbs that stored in chiller (1-5oC), still maintains until 360 days but fresh herbs that stored in AC room (16-20oC), only maintain between 10-12 days before it started to deteriorate. Through hydro-distillation method, essential oil of herbal bath was extracted. The highest amount of essential oils produced were 1% (v/w), extracted from sun dried herbs, kept in freezer and chiller for 150 days, also from oven dried herbs, kept in chiller and AC room for 210, 360 and 150 days respectively. The constant essential oil yields produced from extracted oven dried herbs, kept in the chiller for 0-150 days which was 0.625% (v/w). After that, kept the herbs for a longer time, gave varied results. From this study, the cultivation of herbs at different types of area is possible to be practiced because factors that affected the herbs growth such as herbs morphology, soil fertility and environmental conditions. Herbs cultivating in herbal garden concept has a bigger potential to explore and can become an alternative way to overcome the issue of lack of herbs material raw and cultivation area. For herbal bath processing, oven drying and chiller storage are recommended to be used to keep the quality maintains up to 360 days.